Gluteal rhabdomyosarcoma in a newborn – A case report - Agarwal, Prakash; Bagdi, R K; Raghupathi, V (Indian Journal of Child Health, 2014)
Rhabdomyosarcoma is the most common soft tissue malignancy of childhood; however, can be seen very rarelyin the neonatal period also. It may arise anywhere in the body; head and neck, and genitourinary regions beingthe most frequent sites. Truncal and gluteal rhabdomyosarcoma is relatively rare occurrence. We report aneonate with embryonal rhabdomyosarcoma arising from the gluteal muscles at birth. Ultrasonography andMagnetic resonance imaging raised the possibility of hemangioma lymhangioma. Total excision was done andchemotherapy given. The child had a recurrence after 6 months where the nodule along with the scar wasexcised. A chemoport was introduced and the child underwent further 4 cycles of chemotherapy afterrecurrence. He is well on 2 years follow up without any disability.